Azo Dye Adsorption onto Cobalt Oxide: Isotherm, Kinetics, and Error Analysis Studies - Hawraa Kassem Hami; Ruba Fahmi Abbas; Shireen Abdulmohsin Azeez; Nedaa Ibrahim Mahdi (Universitas Gadjah Mada, 2021)
The current study focused on utilizing cobalt oxide to eliminate hazardous Eriochrome Black T (EBT) dye. The impact of pH (2, 4, 7, 8, and 10) and temperature (45, 50, and 55 °C) was examined for EBT removal. The results show that the maximum sorption occurred at pH = 2 and that the removal percentage increased with increasing temperature. Five non-linear regression methods were used to predict the best isotherm and kinetic models. A coefficient of non-determination, K2, was very helpful for selecting the RMSD function as a preferable error function among the five methods. Isothermal models to illustrate equilibrium sorption information, the Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich models were used. The results showed that the Langmuir model (R2 = 0.99) was the most favorable, indicating monolayer sorption of EBT occurred. The kinetics models were analyzed using pseudo-first-order and pseudo-second-order whereas the sorption information was well described by the pseudo-second-order model (R2 = 0.99). The results of the thermodynamic study appeared that the adsorption of EBT was endothermic, feasible, spontaneous, and physical adsorption.